The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.18380/szie.colum.2017.4.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Some chemical and physical characteristics of farmed pheasant hens (Phasianus cholchicus) breast meat

Abstract: Ring necked pheasant is the most significant game bird in Hungary. Around 300.000 pheasant harvested (hunted) annually and generally these birds are consumed by the hunters. As there are limited data on the quality of pheasant meat, in the present study we aimed to analyze some physical and chemical properties of it. At 20 weeks of age 63 pheasant hens were exterminated by cervical dislocation and meat, liver, spleen and heart samples were taken. The live weight of the birds was 1045±92g (870 to 1300g). The av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…There are also studies found the breast meat lightness lower. Fernye et al (2017) and Dvořák et al (2007) reported the breast meat lightness of pheasant breast meat to 49.27 and 41.19, respectively. Different factors could have effect on this variation.…”
Section: Resultsmentioning
confidence: 99%
“…There are also studies found the breast meat lightness lower. Fernye et al (2017) and Dvořák et al (2007) reported the breast meat lightness of pheasant breast meat to 49.27 and 41.19, respectively. Different factors could have effect on this variation.…”
Section: Resultsmentioning
confidence: 99%
“…10 days later, sexual dimorphism was observed in the chicks due to their live weight, so they were divided into two groups, taking into account their gender. Before feeding the birds in the morning, they were weighed separately and by accuracy of 0.1 mg in (1,3,6,8,10,12,14,16,18,20,22,24,26,28,30,34,38,42 [18].…”
Section: Dynamic Parametersmentioning
confidence: 99%
“…The studies were conducted on pheasants (Phasıanus colchicus colchıcus) incubated in the vivarium of the Institute. The birds were weighed individually, separately, one by one on an electronic scale (Adventurer Pro) with an accuracy of 0.1 mg, in the first two months of postembryogenesis (1,3,6,8,10,12,14,16,18,20,22,24,26,28,30,34,38,42, 50 and 60 days) before feeding in the morning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…e meat of these birds has valuable nutritional, dietary, and sensory values. It is a rich source of protein and micronutrients (especially selenium and phosphorus) and contains small amount of fat with a low content of saturated fatty acids [1,2]. Due to high levels of vitamins B 6 and B 12 and niacin in pheasant meat, the meat of these birds can be similar to the meat of chickens, geese, or ducks [3,4].…”
Section: Introductionmentioning
confidence: 99%